(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pyogenic granuloma (PG) also known as “Lobular capillary hemangioma,” appears as an overgrowth of tissue due to irritation, physical trauma, or hormonal changes in the oral cavity. this present study is on a series of cases comprising of 49 cases of pyogenic granuloma is the first of its kind reported from Eastern India. Even though patients usually do not report the hospital for pyogenic granuloma unless the lesion is large and incapacitating, such number in four years is not very less. Therefore it may be deduced that pyogenic granuloma is not rare in this part of India.